"z_{xx}+xz_{yy}=0"
Comparing the given equation with the equation
we have
"A=1, B=0, C=x, D=0, E=0, F=0, G=0"
The discriminant is
The given equation is elliptic for all "x>0."
The characteristic equations are given by
"\\dfrac{dy}{dx}=\\dfrac{B+\\sqrt{B^2-4AC}}{2A}=\\dfrac{\\sqrt{-4x}}{2}=i\\sqrt{x}"
Integrating these two equations, we get
"iy+\\dfrac{2}{3}x\\sqrt{x}=c_1" and "-iy+\\dfrac{2}{3}x\\sqrt{x}=c_2"
Assume that
Introducing the transformations "\\alpha=\\dfrac{1}{2}(\\xi+\\eta)" and "\\beta=\\dfrac{1}{2i}(\\xi-\\eta)," we obtain
"\\beta=\\dfrac{1}{2i}(iy+\\dfrac{2}{3}x\\sqrt{x}+iy-\\dfrac{2}{3}x\\sqrt{x})=y"
The transformed equation is obtained by first computing
"\\bar{C}=A\\beta_{x}^2+B\\beta_{x}\\beta_{y}+C\\beta_{y}^2=x"
"\\bar{D}=A\\alpha_{xx}+B\\alpha_{xy}+C\\alpha_{yy}+D\\alpha_{x}+E\\alpha_{y}=\\dfrac{1}{2\\sqrt{x}}"
"\\bar{E}=A\\beta_{xx}+B\\beta_{xy}+C\\beta_{yy}+D\\beta_{x}+E\\beta_{y}=0"
"\\bar{F}=F=0\\ and\\ \\bar{G}=G=0"
Substitute in the following equation
Thus, canonical form of the given partial differential equation is
Or
"z_{\\alpha\\alpha}+z_{\\beta\\beta}=-\\dfrac{1}{3\\alpha}z_\\alpha"
Comments
Leave a comment